THE IMPORTANCE OF ENHANCING SPEAKING SKILLS IN TEACHING ENGLISH (Konferensiyalar | Conferences, 2024)
The present study is investigated a teaching methodology for English as a foreign language, aiming to offer an effective approach to enhancing speaking proficiency. The main objective of the research is to examine whether project-based learning is effective in teaching students speaking skills at the first year students.